Is Online Media More Popular Than Traditional Media To Advertise a Brand in the Digital Age? - Ade Kusuma; Adiasri Putri Purbantina; Citra Rani Angga Riswari; Ririn Puspita Tutiasri (Jurnal Ilmu Komunikasi, 2020)
The evolution of media played a significant role in influencing the shift in the concept of traditional advertising towards digital advertising. Advertising in traditional media such as electronic and print media is considered less efficient because it requires a considerable budget. Advertising on online media is recognized as being cheaper than traditional media, both production costs or placement fees in the media. This research is qualitative research with a phenomenological approach. Data collection techniques using literature studies, and in-depth interviews with the advertising workers. The results of this study show how the strength of traditional media than online media to advertise a brand in digital age. The online media such as youtube and social media more effective to build brand awareness compared sales impact. In addition, this paper also explain comparasion the power of word of mouth rather than social media influencer effect in digital advertising.